Village Voices '07 a normal harvest - Price, Laurance; Southern pictures (Tanzania Southern Pictures, 2010)
Village Voices was filmed on repeat annual visits to participating families who share their intimate perspectives on rural poverty and provide insights into forces that make it difficult to lift themselves out of poverty. The 5 annual community-focused films fillow the personal stories of a handful of characters in each village over time, while the final disc investigates 8 developmental themes that emanate from these stories.
Keywords: Rural Poverty, Rural areas Families